Is Temporary Employment a Stepping Stone for Unemployed School Leavers? - Elsy Verhofstadt; Christian Goebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Many school-leavers enter the labour market via temporary employment. In this paper we investigate the impact of a temporary employment spell at the start of the career on the transition rate into permanent employment. We compare the case of temporary employment to the hypothetical case of a direct transition from unemployment to permanent employment. In order to control for selective participation in temporary employment we include a large set of explanatory variables which have been especially collected to study school-leavers. We apply the AIC-information criterion to select the appropriate specification for unobserved heterogeneity. Based on the information criteria we conclude that given our data, there is no support for a model with selection in unobserved characteristics. Simulation exercises provide insights into the development of the effect of temporary employment over time. For a sample of unemployed Flemish school-leavers we find that in the short run temporary employment delays the school leaver's transition to permanent employment. However, in the long run temporary employment acts as a stepping stone and decreases the duration until permanent employment.
Keywords: J41; J08; J64; 330; temporary employment; school leavers; labour market policy; Absolventen; Befristeter Arbeitsvertrag; Berufliche Integration; Flandern; Belgien